2013
DOI: 10.1371/journal.ppat.1003671
|View full text |Cite
|
Sign up to set email alerts
|

Parvoviruses Cause Nuclear Envelope Breakdown by Activating Key Enzymes of Mitosis

Abstract: Disassembly of the nuclear lamina is essential in mitosis and apoptosis requiring multiple coordinated enzymatic activities in nucleus and cytoplasm. Activation and coordination of the different activities is poorly understood and moreover complicated as some factors translocate between cytoplasm and nucleus in preparatory phases. Here we used the ability of parvoviruses to induce nuclear membrane breakdown to understand the triggers of key mitotic enzymes. Nuclear envelope disintegration was shown upon infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 69 publications
4
86
0
Order By: Relevance
“…We did not observe complete inhibition of nuclear entry at this time point, suggesting either reversible inhibition of nuclear import by WGA, which has previously been reported (73), or an alternative, NPC-independent pathway that is utilized by rAAV2. The classical import pathway described herein for rAAV2 differs from the mechanism of nuclear entry proposed by Cohen et al for a related parvovirus, MVM (45), and also recent findings describing nuclear envelope breakdown of permeabilized HeLa cells by AAV2 that had been acidified and then neutralized (50). Future work is required to understand how the acidification and neutralization of rAAV2 mediates nuclear entry under physiological subcellular trafficking conditions.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We did not observe complete inhibition of nuclear entry at this time point, suggesting either reversible inhibition of nuclear import by WGA, which has previously been reported (73), or an alternative, NPC-independent pathway that is utilized by rAAV2. The classical import pathway described herein for rAAV2 differs from the mechanism of nuclear entry proposed by Cohen et al for a related parvovirus, MVM (45), and also recent findings describing nuclear envelope breakdown of permeabilized HeLa cells by AAV2 that had been acidified and then neutralized (50). Future work is required to understand how the acidification and neutralization of rAAV2 mediates nuclear entry under physiological subcellular trafficking conditions.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, a PDZbinding domain was discovered on the N terminal of VP1 that was shown to be important for nuclear entry of wt AAV2 (49). While the current study was under review, a recent study revealed that AAV2 that had been acidified and then neutralized could cause nuclear envelope breakdown in permeabilized HeLa cells (50). As in vitro assays become more harmonized with respect to physiological infection, these results, taken together, suggest that AAV may utilize multiple import mechanisms to gain access to the nucleus, or that the mechanism of nuclear entry might vary for wt AAV2 and AAV vectors.…”
Section: A Deno-associated Virus (Aav) Is a Dependovirus In The Familymentioning
confidence: 87%
See 1 more Smart Citation
“…To induce perforation of the nuclear membranes without mitosis, we made use of parvovirus H1, a small DNA virus known to enter the nucleus by inducing holes in the NE [64]. These hole are large enough to allow sudden entry of antibodies into the nucleus and, at least in some cells, chromatin leakage into the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…In early steps, incoming capsids need to either enter the nucleus or at least dock to the nuclear membrane to inject the viral genome into the nucleus (18)(19)(20)(21). In late steps of infection, newly synthesized capsid proteins rapidly assemble into trimers before nuclear transport (22,23).…”
mentioning
confidence: 99%